Drug treatments for the neuropsychiatric complications of Parkinson's disease. (December 2012) - Connolly, Barbara S; Fox, Susan H
Psychiatric symptoms are now well described in Parkinson's disease (PD). Most are due to the disease pathology with exacerbation caused by dopaminergic treatment. Anxiety and depression may predate the onset of motor symptoms and can continue to occur with advancing disease. In patients with parkinsonism, well-formed hallucinations are highly specific for PD and some patients may progress to other psychotic symptoms. Cognitive impairment, ranging from mild impairment to dementia is common. Management of these symptoms involves initial recognition and secondly, appropriate medications. Pharmacological treatments are not specific for PD and are the same as those currently used in nonPD populations. The choice of agent is determined by a balance between potential benefit versus side effects, mostly in terms of worsening motor PD symptoms. This article will review current treatment approaches to mood disorders, psychosis and cognitive problems in PD, as well as management of dopamine-induced impulse control disorders.